Transforming Museum Experience Using User-Experience Based New Product Development - Hapsari, Larasati; Iskandar, Budi Permadi (Journal of Business and Management, 2016)
Abstract. Museum is a public space in which the society can find both educational and recreational values. According to Hooper-Greenhill (1999), museum should function as one of educational media for society, therefore the relevance of its product and its function is considered important. However, along with the vast development modern civilization in big cities in Indonesia, museum becomes less popular compared to other public spaces such as mall. The problem lies on the unninovative product presented in museum, which is described as stagnant, not interactive and unattractive by its target market: children and family. Therefore, researcher attempt to solve the problem through proposing new product development (NPD) method. In today’s world, industrial-age product development methods which only focused on feature is proven to be inefective, leaving company to build something people don’t need. Thus, new product development method is invented, putting user research as first step of the entire product development process. Taking also into account, a great product is not merely build based on feature, but experience. That’s where researcher need to consider User Experience as the core of the product. Therefore, this research is conducted to examine the first step of product development process based on Crawford & Benedetto Model with focus on User Experience. Bandung Geological Museum is choosen as the site of research based on its significancy toward West Java people, specifically Bandung people. Researcher attempt to asses current need of museum visitors compared to the current experience presented using Laddering Method interview proposed by Zaaman & Abeele in 2010 based on following aspect: motivation, feel, thought and learn. Later, researcher presented them with three different level of product interactivity based on Fragidis et al model proposed in 2014. The result shows that the most desireable experience desired by children as Bandung Geological Museum visitors are related to these keyword: co-creation interactivity, familiarity and dinosaurs-themed.As a response to the finding, researcher propose an idea of creating buildable paper dinosaurs mask with voice changer feature. This idea is a result of brainstorming session, produce and build with PT Sembilan Matahari, a creative design studio based in Bandung.Keyword: museum, user experience, new product development(NPD)